Cardiovascular adverse events associated with antibody-drug conjugates (ADCs): a pharmacovigilance study based on the FAERS database - PingPing Long; Siyu Li; Lingyun Pan; Yuanqiang Wang; Wanyi Chen; Xiaoxiao Wang (Frontiers Media S.A., 2024)
ObjectiveAs a novel drug formulation, antibody drug conjugates (ADCs) are widely used in various types of cancer. However, clinically, there is a lack of attention to the CVD produced by them, as well as a lack of research on the real-world situation. Using the Food and Drug Administration Adverse Event Reporting System (FAERS) database, to ensure its clinical safety application, we analyzed post-marketing data on antitumor ADCs to identify risk factors and drugs associated with the risk of cardiovascular events.Research design and methodsWe used OpenVigil 2.1 to conduct a database query for adverse events (AEs) reported to the FAERS database between the time the drug was launched and the second quarter of 2023. Cardiovascular adverse events (AEs) were grouped into fourteen narrow categories using the Standardized Medical Dictionary for Regulatory Activities (MedDRA) Queries (SMQs), and the reporting odds ratio (ROR) and the proportional reporting ratio (PRR) for reporting the association between different drugs and cardiovascular disease (CVD) risk were calculated.ResultsIn the FAERS database, 1863 AEs associated with CVD we studied were identified in patients receiving ADC therapy. Most reports came from people aged ≥65, but a significant number of cases were found to be unknown. The number of patients with antibody-drug conjugates (ADCs)-related CVD cases aged <18 years, 18-64 years, and≥ 65 years was 52 (2.79%), 586 (31.45%), and 613 (32.90%), respectively. The proportion of female patients (834, 44.77%) was higher than that of male patients (752, 40.37%). Death (770 reports), disability (9 reports), Hospitalization initial or prolonged (407 reports), and life-threatening reactions (187 reports). Of the 770 deaths reported, 103 (31.7%) were associated with brentuximab vedotin, 10 (24.4%) with sacituzumab govitecan, 22 (19.3%) with enfortumab vedotin, and 35 (34.7%) with trastuzumab emtansine.49 (41.2%) cases were associated with polatuzumab vedotin, 62 (29%) with trastuzumab deruxtecan, 423 (54.3%) with gemtuzumab ozogamicin, and 66 (38.8%) with inotuzumab ozogamicin. In a disproportionate number of SMQS, cardiac failure (n = 277) and embolic and thrombotic events, venous (n = 446) were the most frequently reported CVD-related AEs in ADCs.ConclusionBy mining the FAERS database, we provided relevant information on the association between ADC use and cardiovascular-associated AEs. ADCs were associated with increased cardiovascular toxicity, deserving distinct monitoring and appropriate management. Further research is needed to confirm these findings and assess causality.